2022
DOI: 10.1002/smll.202204747
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Delivery to Golgi Apparatus and On‐Site Formation of Subcellular Drug Reservoir for Cancer Metastasis Suppression

Abstract: As the foremost cause of cancer‐related death, metastasis consists of three steps: invasion, circulation, and colonization. Only targeting one single phase of the metastasis cascade may be insufficient since there are many alternative routes for tumor cells to disseminate. Here, to target the whole cascade of metastasis, hybrid erythrocyte and tumor cell membrane‐coated nanoparticle (Hyb‐NP) is designed with dual functions of increasing circulation time and recognizing primary, circulating, and colonized tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Upon NIR laser irradiation, tumor growth and recurrence in TNBC mice, through the induction of tumor ablation and anti-angiogenesis, were more thoroughly repressed by HCNPs than by free IR780, DOX, or naked NPs. In another example, therapeutic microR- Cancer cell/platelet miRNAs TNBC 2021 [125] Red cell/cancer cell Fe 3 O 4 ICG Ovarian cancer 2021 [53] Red cell/cancer cell PLGA Monensin Orthotopic breast cancer 2023 [128] Red cell/platelet PLGA Anti-CXCR2 Hypercholesterolemic 2023 [129] TNBC: triple-negative breast cancer; DOX: doxorubicin; ICG: indocyanine green; PLGA: poly (lactic-co-glycolic acid).…”
Section: Hybrid Cell Membrane-coated Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon NIR laser irradiation, tumor growth and recurrence in TNBC mice, through the induction of tumor ablation and anti-angiogenesis, were more thoroughly repressed by HCNPs than by free IR780, DOX, or naked NPs. In another example, therapeutic microR- Cancer cell/platelet miRNAs TNBC 2021 [125] Red cell/cancer cell Fe 3 O 4 ICG Ovarian cancer 2021 [53] Red cell/cancer cell PLGA Monensin Orthotopic breast cancer 2023 [128] Red cell/platelet PLGA Anti-CXCR2 Hypercholesterolemic 2023 [129] TNBC: triple-negative breast cancer; DOX: doxorubicin; ICG: indocyanine green; PLGA: poly (lactic-co-glycolic acid).…”
Section: Hybrid Cell Membrane-coated Nanoparticlesmentioning
confidence: 99%
“…This formulation has demonstrated success in reducing pulmonary metastatic nodules in an orthotopic breast cancer model, which shows significant Golgi apparatus drug reservoir formation and greater inhibition of metastasis in vivo than free monensin by targeting multiple phases of the metastasis cascade. [128] It is noteworthy that this work specifically compared pegylation, single-membrane cloaking, and HCMs cloaking for the corresponding NPs core directly. In this in-stance, HCNPs displayed excellent inhibition of metastasis.…”
Section: Hybrid Cell Membrane-coated Nanoparticlesmentioning
confidence: 99%
“…Artificial biomimetic coatings (e.g., cell membrane coated particles, , reconstructed extracellular vesicles , ) could greatly improve the drug delivery efficiency of NDDS via influencing the nanobio interaction. , Recent research has demonstrated that the negative impacts of PCs can be surmounted and converted to beneficial impacts based on the artificial reconstruction of PCs coatings. ,, For example, Liu et al found that the key to slowing the clearance of viral vaccines (OVs) from the bloodstream was to restrict the natural formation of viral-PCs in the plasma. Therefore, they used serum proteins to form artificial virus-PCs on OVs, which prevented the formation of viral-PCs and reduced clearance rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, for some tumors with complex microenvironment such as TNBC and pancreatic cancer, single cell membrane modification might not be able to achieve effective drug delivery [19] , [20] . Of note, hybrid cell membranes coated nanoparticles have shown significant advantages in integrating of multiple functions and cascade targeting [21] , [22] , [23] . Although they have been applied for enhancing the drug accumulation at the target sites and caused significant inhibition of tumor growth, the ability for hybridization of CAFs and cancer cell membrane for the sequential delivery in TNBC therapy has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%